2017
DOI: 10.14254/2071-8330.2017/10-3/13
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to the development of cognitive process dimensions in financial literacy: an empirical study

Abstract: Abstract. The article explores various approaches to the development of cognitive process dimensions in financial literacy. It is based on the empirical research of the financial literacy levels among 1,207 fifteen-year-old Czech students compared with 18 countries worldwide (OECD, 2014a). Applying the regression model, the study has examined the strength of the relationship between the actual financial competence of 284 Czech students aged 17-18, studying economic disciplines, and their school performance. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Student outcomes are therefore not an appropriate tool for assessing cognitive abilities, as they do not provide correct information value. The academic achievement says more about the student's current readiness in the given subject (Berková & Krpálek, 2017). This is also proven by international research (Kiliyanni & Sivaraman, 2016;Little, Miyashita, Karasawa, Mashima, Oettingen, Azuma, & Baltes, 2003) that has shown that students with higher academic achievement can not often think deeper, search for relations, structure, and put it together as opposed to those students whose academic achievement is weak.…”
Section: Theoretical Foundationmentioning
confidence: 85%
See 2 more Smart Citations
“…Student outcomes are therefore not an appropriate tool for assessing cognitive abilities, as they do not provide correct information value. The academic achievement says more about the student's current readiness in the given subject (Berková & Krpálek, 2017). This is also proven by international research (Kiliyanni & Sivaraman, 2016;Little, Miyashita, Karasawa, Mashima, Oettingen, Azuma, & Baltes, 2003) that has shown that students with higher academic achievement can not often think deeper, search for relations, structure, and put it together as opposed to those students whose academic achievement is weak.…”
Section: Theoretical Foundationmentioning
confidence: 85%
“…Slightly negative correlation of variables means that students with higher result in the school test in Corporate Economy, which was focused only on the cognitive dimensions of the lower order, were less successful in tasks that reflected the dimensions included in factor 2 and vice versa. This proves that academic achievement reflects more the student's current knowledge in the given subject (Berková & Krpálek, 2017). In other words that students with higher academic achievement cannot often think more deeply, look for relations, structures, and put them in one complex as opposed to those students whose performance at school is weak (Little, Miyashita, Karasawa, Mashima, Oettingen, Azuma, & Baltes, 2003;Kiliyanni & Sivaraman, 2016).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is a virtual company that is guided as if it actually existed. It simulates real processes, products and services (Berkova, Krpalek, 2017).…”
Section: Cultivating Human Capital As An Education Focused On Entreprmentioning
confidence: 99%
“…Financial literacy and skill are an active area of research in the field (Berková & Krpálek, 2017). Psychology provides evidence that children in upper primary schools can understand basic economic concepts and managing their money and can thus be taught about personal finances (Otto, Schots, Westerman, & Webley, 2006).…”
Section: Introductionmentioning
confidence: 99%